A review of security risks and countermeasures in containers - Morales Rocha, Victor Manuel (2021)
Containers are environments that allow software developers to package applications, along with their libraries, dependencies, and all the resources necessary for their operation. Due to the advantages of containers, compared to virtual machines, their use has increased in recent years. However, the nature of containers to share both, the resources, and the kernel of the host system, produces a variety of security problems. This paper describes how application containers work, to latter present a review of the security risks to this technology, as well as the countermeasures to mitigate them. A classification has been made of the risks as well as the security mechanisms used in this environment. Finally, according to different works that were analysed, a relation of the risks and the corresponding mechanisms to counteract them is presented.